2022
DOI: 10.3390/nu14194087
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin in Endometriosis: Mechanistic Understanding and Clinical Insight

Abstract: Endometriosis is defined as the development of endometrial glands and stroma outside the uterine cavity. Pathophysiology of this disease includes abnormal hormone profiles, cell survival, migration, invasion, angiogenesis, oxidative stress, immunology, and inflammation. Melatonin is a neuroendocrine hormone that is synthesized and released primarily at night from the mammalian pineal gland. Increasing evidence has revealed that melatonin can be synthesized and secreted from multiple extra-pineal tissues where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 206 publications
0
15
0
3
Order By: Relevance
“…Melatonin (N-acetyl-5-methoxytryptamine) is a naturally occurring peptide hormone secreted by the pineal gland and multiple extra-pineal tissues (e.g., uterus, ovaries, and placenta) involved in the regulation of response to darkness, immune responses, inflammation, and microenvironmental angiogenesis [ 108 ]. Therefore, it is involved in the regulation of the sleep cycle and in multiple biological functions such as the metabolism of lipids, saccharides and the immune response [ 109 ].…”
Section: Antioxidant Systems In Female Reproductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Melatonin (N-acetyl-5-methoxytryptamine) is a naturally occurring peptide hormone secreted by the pineal gland and multiple extra-pineal tissues (e.g., uterus, ovaries, and placenta) involved in the regulation of response to darkness, immune responses, inflammation, and microenvironmental angiogenesis [ 108 ]. Therefore, it is involved in the regulation of the sleep cycle and in multiple biological functions such as the metabolism of lipids, saccharides and the immune response [ 109 ].…”
Section: Antioxidant Systems In Female Reproductionmentioning
confidence: 99%
“…Therefore, it is involved in the regulation of the sleep cycle and in multiple biological functions such as the metabolism of lipids, saccharides and the immune response [ 109 ]. Melatonin was shown to decrease OS, inflammation processes, and apoptosis [ 108 ]. It is directly involved in the detoxification of ROS and NOS, and is indirectly involved in the stimulation of enzymatic antioxidants and the suppression of pro-oxidants [ 110 ].…”
Section: Antioxidant Systems In Female Reproductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Melatonin is a chemical that functions as both a direct antioxidant and a modulator of the mechanisms defending cells against oxidative stress. It was initially utilized in reproductive medicine to treat endometriosis and adenomyosis-related infertility [33,34,127,128]. Since then, fresh research has shown how melatonin may delay the aging of the ovary [36].…”
Section: Mitochondrial Support Therapymentioning
confidence: 99%